If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(4x + -1) = 3x + -11 Reorder the terms: 3x + -1(-1 + 4x) = 3x + -11 3x + (-1 * -1 + 4x * -1) = 3x + -11 3x + (1 + -4x) = 3x + -11 Reorder the terms: 1 + 3x + -4x = 3x + -11 Combine like terms: 3x + -4x = -1x 1 + -1x = 3x + -11 Reorder the terms: 1 + -1x = -11 + 3x Solving 1 + -1x = -11 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 1 + -1x + -3x = -11 + 3x + -3x Combine like terms: -1x + -3x = -4x 1 + -4x = -11 + 3x + -3x Combine like terms: 3x + -3x = 0 1 + -4x = -11 + 0 1 + -4x = -11 Add '-1' to each side of the equation. 1 + -1 + -4x = -11 + -1 Combine like terms: 1 + -1 = 0 0 + -4x = -11 + -1 -4x = -11 + -1 Combine like terms: -11 + -1 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| t^2-35t+216=0 | | 1.74k-7.2-6.3k=7.848 | | 93=3(1+8x) | | (x-1)(x+3)=(x+2)(x+3)+1 | | v+4+v=8 | | -1a+54=5+13.89 | | 3x^2+23x-70= | | -1+54=5+13.89 | | 5x+7=7y+10 | | 5-22=-(x-4) | | 14+(-15)=1 | | 7.5r+11=24 | | 11y+9=15y-23 | | 9-2+2(5-1)= | | 3x-5(-2-16)=31 | | 6x-18=-5 | | -14+6b+7-2b=3+6a | | 2X-12+8=34 | | A=zv+x | | A=zv | | x^3+19x^2+60x=0 | | 5x+3(-4-8)=32 | | 3=7+1x | | 13(-7p-2)= | | 3a+5b=39 | | -5(2y-10)-y=-2(y-4) | | .06y+.11(5000-y)=.33y | | 6a-5=4a-2 | | -70=6(m+6)+8(-3m-2) | | 1b-7=-2 | | -2(-5x-4)=48 | | 3(c-5)=25 |